Kewenangan Otoritas Jasa Keuangan (OJK) Melakukan Penyidikan: Analisis Pasal 9 Huruf C Undang-Undang Nomor 21 Tahun 2011 Tentang Otoritas Jasa Keuangan - Serlika Aprita (Universitas Batanghari Jambi, 2021)
In Law No. 21 of 2011 concerning the Financial Services Authority authorizes the OJK to carry out investigations. Investigation is one of OJK's supervisory duties as referred to in Article 9 letter c of the OJK Law which reads: